Finite-size effects and thermodynamic limit in one-dimensional Janus fluids. (26th October 2021) - Fantoni, R; Maestre, M A G; Santos, A
Abstract: The equilibrium properties of a Janus fluid made of two-face particles confined to a one-dimensional channel are revisited. The exact Gibbs free energy for a finite number of particles N is exactly derived for both quenched and annealed realizations. It is proved that the results for both classes of systems tend in the thermodynamic limit ( N → ∞) to a common expression recently derived (Maestre and Santos 2020 J. Stat. Mech. 063217). The theoretical finite-size results are particularized to the Kern–Frenkel model and confirmed by Monte Carlo simulations for quenched and (both biased and unbiased) annealed systems.